Viscoelastic response of the lateral side of the ankle to cyclic inversion: A time course analysis. Issue 6 (19th March 2014) - Malmir, K.; Olyaei, G. R.; Talebian, S.; Jamshidi, A. A.
<x xml:space="preserve">Abstract</x> Although important, viscoelastic behavior of the ankle's lateral side has rarely been studied. The present study assesses the viscoelastic behavior during cyclic inversions. Eighteen recreationally active healthy males underwent 40 passive cyclic inversions using a Biodex dynamometer at 5 °/s through 80% of maximum range of motion. Energy absorption and restitution and dissipation coefficient were calculated for each repetition. Changes in the mean of the dependent variables for repetitions 1 (R1), R5, R10, R15, R20, R25, R30, R35 and R40 were compared by three one‐way analyses of variance with repeated measures. There was a significant difference between the means of energy absorption for the selected repetitions from R1 to R20 (P < 0.01), but there was no significant difference between them from R20 to R40 (P > 0.05). There was no significant difference between the means of energy restitution for the selected repetitions (P > 0.05). Whereas there was no significant difference consecutively between the means of dissipative coefficient for the selected repetitions (P > 0.05), there was a significant difference between the means of R30 or R40 relative to the baseline (P < 0.005). The decrease in the energy absorbed and the dissipation coefficient following repeated inversions may be due to the slippage of collagen fibers. The decrease in the shock absorbing ability of the tissues may expose them to injury.